Information Literation about Reproductive Health in Junior High School Teenagers - kustin kustin (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Health literacy is the ability to obtain, process, and understand basic health information and health services, as well as one's ability to apply this health information to one's life. Health literacy is an important aspect for a person in empowering health. One form of health literacy can be an understanding of reproductive health, especially in junior high school adolescents. The purpose of this study was to find out the description of information literacy about reproductive health in junior high school adolescents. The research design is a descriptive survey. The sampling technique was carried out by random sampling with a sample of 348 respondents. The results showed that 95 respondents aged 15 years (27%), 184 respondents (56%) were female, 287 respondents (82%) came from the Madurese, 248 respondents (71%) lived in the suburbs. While sources of information were 266 respondents (83%) from print media, 348 respondents (100%) from social media, 216 respondents (52%) from billboards, 345 respondents (99%) from the internet and 294 respondents (84%) from media electronic. While adolescent literacy regarding adolescent reproductive health was obtained by 48 respondents (13%), sufficient literacy by 124 respondents (36%) and insufficient literacy by 176 respondents (51%). The level of literacy is very important in influencing the way of life of adolescents with healthy reproductive health so that they do not fall into wrong associations and are detrimental to adolescents.